TIMP-1 in the prognosis of patients who underwent coronary artery bypass surgery: a 12-year follow-up study - Huang, Jui-Tzu; Sung, Shih-Hsien; Hsu, Chiao-Po; Chiang, Chern-En; Yu, Wen-Chung; Cheng, Hao-Min; Huang, Cheng-Hsiung (Frontiers in Cardiovascular Medicine, 2023)
Matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) have been linked to clinical outcomes in patients with coronary artery disease (CAD). However, the prognostic values of TIMP-1 among patients with CAD undergoing coronary artery bypass grafting (CABG) has not been elucidated. We aimed to investigate the correlations of TIMP-1 with high-sensitivity Creactive protein (hs-CRP) and N-terminal pro-brain natriuretic peptide (NT-proBNP) in the long-term prognosis among consecutive patients undergoing CABG.Overall, 234 patients (age: 70.4 ± 10.5 years, 84.6% men) with CAD undergoing CABG were prospectively enrolled. Preoperative levels of MMPs, TIMP-1, hs-CRP, and NT-proBNP were recorded. Major adverse cardiovascular events (MACE) were defined as nonfatal myocardial infarction, nonfatal stroke, and cardiovascular death.During the median follow-up of 12.1 years, 120 deaths were recorded. The deceased were older, had more manifest acute coronary syndrome (ACS), lower left ventricular ejection fraction (LVEF), and estimated glomerular filtration rate (eGFR), but significantly higher MMP13, TIMP-1, hs-CRP, and NT-proBNP compared with the survivors. After accounting for age, sex, manifest ACS, eGFR, LVEF, total cholesterol, and triglycerides, TIMP-1 (hazard ratio and 95% confidence intervals per SD: 1.506, 1.183-1.917), hs-CRP (1.349, 1.183-1.561), and ) were all independently associated with total mortality. The mediation analysis revealed that the mortality risks of TIMP-1 were partially mediated by NT-proBNP (62.2%) and hs-CRP (25.3%). The associations of TIMP-1 with MACE were partially mediated by NT-proBNP (54.4%), but not hs-CRP.TIMP-1 was an independent predictor for long-term outcomes after CABG, with possible roles in subclinical inflammation and cardiac remodeling after the surgery.